Magnetic fields exposure from high-voltage power lines and risk of amyotrophic lateral sclerosis in two Italian populations. Issue 7 (2nd October 2017) - Vinceti, Marco; Malagoli, Carlotta; Fabbi, Sara; Kheifets, Leeka; Violi, Federica; Poli, Maurizio; Caldara, Salvatore; Sesti, Daniela; Violanti, Silvia; Zanichelli, Paolo; Notari, Barbara; Fava, Roberto; et al.
Abstract: The aetiology of amyotrophic lateral sclerosis (ALS), a rare and extremely severe neurodegenerative disease, has been associated with magnetic fields exposure. However, evidence for such a relation in the general population is weak, although the previous null results might also be due to exposure misclassification, or a relationship might exist only for selected subgroups. To test such a hypothesis we carried out a population-based case-control study in two Northern and Southern Italy regions, including 703 ALS cases newly diagnosed from 1998 to 2011 and 2737 controls randomly selected from the residents in the study provinces. Overall, we found that a residence near high-voltage power lines, within the corridors yielding a magnetic fields of ≥0.1 μT, was not associated with an excess disease risk, nor did we identify a dose-response relationship after splitting the exposed corridor according to the 0.1, 0.2 and 0.4 μT cut-points of exposure. These results were confirmed taking into account age at onset, period of diagnosis, sex, geographical area, and length of exposure. Overall, despite the residual possibility of unmeasured confounding or small susceptible subgroups not identified in our study, these results appear to confirm that the exposure to magnetic fields from power lines occurring in the general population is not associated with increased ALS risk.